Huge mediastinal ancient schwannoma causing acute respiratory failure: a case report - Hsuan-Ying Huang; Chien-Ming Lo; Hung-I Lu; Jen-Ping Chang (Journal of Cardiothoracic Surgery, 2024)
Abstract Benign mediastinal tumor is usually asymptomatic and exhibits uncomplicated clinical course. Posterior mediastinal schwannoma is common, but a huge benign tumor causing acute respiratory failure due to mass effect is unusual. We present a patient who suffered from acute respiratory failure due to huge mediastinal mass effect and improved after en bloc surgical resection. A 56-year-old woman had no history of systemic disease, but experienced general discomfort and malaise for several months. She was referred to our emergency department after developing sudden respiratory failure. Intubation was performed with ventilator support and she was admitted to the intensive care unit. Chest radiograph and computed tomography showed a huge mass over the left pleural cavity causing left lung, heart, and mediastinal compression. After en bloc resection, she was weaned off the ventilator successfully and was discharged at 24 days after the operation. Postoperative outpatient follow-up showed no symptoms. Mediastinal ancient schwannoma is a rare posterior mediastinal benign tumor. However, mass effect might lead to lethal complications. En bloc resection is necessary for curative treatment.